1995
DOI: 10.1128/jcm.33.7.1716-1719.1995
|View full text |Cite
|
Sign up to set email alerts
|

Use of amplified fragment length polymorphism in molecular typing of Legionella pneumophila and application to epidemiological studies

Abstract: A novel method for molecular typing of organisms, amplified fragment length polymorphism analysis, was tested for its suitability in epidemiological studies in medical microbiology. Amplified fragment length polymorphism analysis, originally developed for typing crop plants, consists of a simple restriction-ligation reaction and a subsequent PCR amplification. In a single-step reaction, the genomic DNA is digested and the restriction fragments are ligated to specially constructed adapters. PCR amplification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
7

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 6 publications
0
53
0
7
Order By: Relevance
“…AFLP analysis was carried out according to the original method described by Valsangiacomo et al (21) using AFLPPstI-G as a selective primer.…”
Section: Genotypingmentioning
confidence: 99%
“…AFLP analysis was carried out according to the original method described by Valsangiacomo et al (21) using AFLPPstI-G as a selective primer.…”
Section: Genotypingmentioning
confidence: 99%
“…Selective amplification by PCR of sets of these fragments is achieved using primers corresponding to the contiguous base sequences in the adapter restriction site plus one or more nucleotides in the original target DNA. The adapters are designed with an additional base pair in the restriction site [13], so that after ligation to the restricted fragment, the base pair can be eliminated. The resulting PCR-amplified DNA fragments may then be analyzed by polyacrylamide gel electrophoresis (PAGE) or by agarose gel electrophoresis (AGE).…”
Section: Introductionmentioning
confidence: 99%
“…AFLP analysis involves digestion of cellular DNA with two restriction enzymes; ligation of speci¢c oligonucleotide adaptors to the pertinent restriction sites; PCR ampli¢cation using primers speci¢c to the relevant restriction site/adaptor sequence; and separation and detection of the PCR-ampli¢ed fragments. Several studies have shown that AFLP is a highly sensitive method for characterising a wide range of bacterial pathogens, including Legionella pneumophila [11], Aeromonas spp. [10], and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. However, AFLP requires optimisation for di¡erent organisms to account for genomic di¡erences (notably genome size and G+C content), and also to ensure the resolving power of the electrophoretic detection system employed is used to its full potential [10,11]. Here we describe a method suitable for AFLP ¢ngerprinting of C. jejuni and C. coli and evaluate its potential for molecular epidemiological studies of these taxa.…”
Section: Introductionmentioning
confidence: 99%